Embedding local culture in social studies: pathways to strengthen social-emotional learning in primary education - Niman, Erna Mena (Frontiers in Education, 2025)
Social Science learning in elementary school plays a strategic role in developing social-emotional skills in students, but the orientation remains more normative in nature rather than contextual. This study attempts to examine how the employment of local culture in social studies learning can assist in developing social emotional learning (SEL). This qualitative case study design involved six teachers from six elementary schools who were chosen according to criteria of more than 10 years of experience, driving teacher status, and schools with a minimum B accreditation. Data collection techniques were carried out through observation, in-depth interviews, and document study (lesson plans and syllabus), and then analyzed using a thematic analysis approach based on the four principles of SEL, with validation through data source triangulation. The findings indicate that local culture has fostered the development of social awareness, self-management, social relations, and responsible decision-making in a constructive manner, but the component of self-awareness is not yet optimally supported in the learning process. This research adds value to the formulation of a social studies learning model founded upon local culture, not merely being cultural in nature, but also in supporting the development of students' character in a comprehensive manner through the development of social-emotional dimensions.